2014
DOI: 10.11113/jt.v71.3756
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Rainfall on Travel Speed

Abstract: The road network is particularly susceptible to adverse weather with a range of impacts when different weather conditions are experienced. Adverse weather often leads to decreases in traffic speed and subsequently affects the service levels. The paper is aimed at investigating the impact of rainfall on travel speed and quantifying the extent to which travel speed reduction occurs. Empirical studies were conducted on principle road in Terengganu and Johor, respectively for three months. Traffic data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It can be divided into two major categories: direct analysis of the impact on traffic characteristics and optimization of existing traffic models based on rainfall intensity. For the first kind, Mashros et al [4] quantified the impact of rainfall on travel velocity, and the results showed that all percentile velocities decreased from the lowest 1% in light rain to the highest 14% in heavy rain. Rahman and Lownes [5] studied the influence of rainfall on driver behaviour under car following conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It can be divided into two major categories: direct analysis of the impact on traffic characteristics and optimization of existing traffic models based on rainfall intensity. For the first kind, Mashros et al [4] quantified the impact of rainfall on travel velocity, and the results showed that all percentile velocities decreased from the lowest 1% in light rain to the highest 14% in heavy rain. Rahman and Lownes [5] studied the influence of rainfall on driver behaviour under car following conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that, especially in Hong Kong and other cities in Asia, rainfall intensity should be considered in the design, operation, and evaluation of road facilities because annual rainfall intensity is relatively high in these cities. Mashros et al [26] estimated the effects of rainfall on travel speed and degree of reduction in speed using data of three months. They divided rainfall intensity into four levels and graph reduction of traffic speed at the 15th, 50th, and 85th percentiles according to rainfall intensity increase.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong and other Asian cities, it is suggested that rainfall intensity should be considered in the design, operation, and evaluation of road facilities because the average annual rainfall intensity is relatively high. Mashros et al [3] estimated the effect of rainfall on the moving speed and the extent of the speed decrease using three months of data. Thus, the rainfall intensity is divided into four stages and a graph shows that the moving speed decreases in percentiles of 15, 50, and 85 as the rainfall intensity increases.…”
Section: Introductionmentioning
confidence: 99%